Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin. Issue 8 (17th November 2019) - Sun, X. L.; Lin, C. Y.; Zhang, X. G.; Lin, J. L.; Zhao, Z. X.; Huang, D. W.; Duan, D. P.
Abstract: The characteristics and distribution of clay minerals and their effects on reservoir quality in the Huagang sandstones in the Xihu Sag, East China Sea Basin were studied by using X-ray diffraction, casting thin-sections, scanning electron microscopy, electron microprobe analysis, fluid inclusion analysis, constant-rate mercury injection and nuclear magnetic resonance. Clay minerals consist of kaolinite, chlorite, illite and illite–smectite mixed layer (I/S); kaolinite forms from dissolved feldspars, chlorite occurs as clay coatings that are transformed from clay precursors owing to the flocculation of suspended detrital clays or the crystallisation of pore fluids, and illite forms from the illitisation of detrital smectite, authigenic kaolinite and K-feldspars. Clay distribution is controlled by sedimentary environments, burial history and lithologies. Typical reservoirs in the western sub-sag are thin and developed in braided river facies at relatively shallow burial depths with clays dominated by kaolinite. However, typical reservoirs in the central inversion tectonic zone are thicker and developed in a braided delta front facies at deeper burial depths with clays mainly consisting of chlorite, illite and I/S. High-quality reservoirs are characterised by coarse granularity, high quartz content and low clay content with widespread development of chlorite coatings that inhibit quartz cements at low temperatures. At higher temperatures, the high-quality reservoirs develop more pores providing growth space for quartz cements and result in the coexistence of chlorite coatings and quartz cements. The high-quality reservoirs are controlled by their lithological characteristics rather than chlorite coatings. Illite and I/S clays create severe damage to reservoirs by reducing the size and connectivity of pore-throats.